ICT Integration in Primary School Classrooms in the time of Pandemic in the Light of Jean Piaget's Cognitive Development Theory - Osias Kit T. Kilag; Renan Ignacio; Evelyn B. Lumando; Geraldine U. Alvez; Cara Frances K. Abendan; Niña Michelle P. Quiñanola; John Michael Sasan (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
Since the pandemic's impact on the world's educational systems, the use of digital platforms has increased significantly. The authors of this research offer useful teaching strategies that can be applied in the classroom and may be employed in the event of a future pandemic or a return to the more conventional learning and teaching environment. Considering the cognitive development articulated by Jean Piaget and with and uses ICT integration. The study was conducted by the authors using descriptive qualitative research and thematic analysis. The narrative and theme analysis that the authors undertook also enabled them to draw insightful inferences from the study's primary source. The findings show that ICT integration is very successful for both teachers and students when seen in the light of Jean Piaget's theory of cognitive development. Additionally, it was found that the teacher's continual ICT learning is one of the crucial components of an effective and successful teaching and learning process. The implementation of policies in the classroom and the strategic use of technology by students must be considered and explored in a future study.